Aggregate Skewness and the Business Cycle - Iseringhausen, Martin; Petrella, Ivan; Theodoridis, Konstantinos (The Review of Economics and Statistics, 2026)
Abstract We develop a data-rich measure of expected macroeconomic skewness in the U.S. economy. Expected macroeconomic skewness is strongly procyclical, mainly reflects the cyclicality in the skewness of real variables, is highly correlated with the cross-sectional skewness of firm-level employment growth, and is distinct from financial market skewness. Revisions in expected skewness lead to business cycle fluctuations nearly indistinguishable from those induced by the main business cycle shock of Angeletos et al. (2020). This result is robust to controlling for macroeconomic volatility and uncertainty, and alternative macroeconomic shocks. Our findings suggest an important role of higher-order dynamics for business cycle theories.